Alexithymia and fibromyalgia: clinical evidence - Di Tella, Marialaura; Castelli, Lorys (Frontiers in Psychology, 2013)
This review proposes a critical discussion of the latest studies investigating the presence of alexithymia in patients with fibromyalgia (FM) and its relation to other psychological disorders. The focus is on the most relevant literature exploring the relationship between FM, a chronic pain syndrome, and alexithymia, an affective dysregulation, largely observed in psychosomatic diseases. The articles were selected from the Medline/Pubmed database using the search terms “Fibromyalgia”, “Alexithymia”, and “Psychological Distress”. Of the seven studies fulfilling these criteria, one found no differences between FM patients and the control group, four found significant differences, with higher levels of alexithymia in the FM sample, while two showed unclear results. Overall, the majority of findings highlighted the high prevalence of alexithymia in FM patients. Future studies should clarify the role of alexithymia in FM, paying attention to two principal aspects: the use, as a control group, of patients with chronic pain conditions but a low psychosomatic component, and the use of other measures, in addition to the Toronto Alexithymia Scale (TAS-20), to assess alexithymia.